PERSEPSI MASYARAKAT MELALUI PENDEKATAN THEORY OF PLANNED BEHAVIOR (TPB) DENGAN NIAT PENGOBATAN SAKIT GIGI DI KELURAHAN PEMURUS BARU - Rinda Fitrianor; Melviani Melviani; Sismeri Dona (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: Perceptions about treatment lead to varied use of drugs including the use of toothache drugs, the experience of information received by the community affects perceptions about treatment so that the role of individuals in making decisions about toothache treatment varies, so it is necessary to see how people's perceptions with the intention of taking treatment are. toothache using a Theory of Planned Behavior approach. The Aim Of The Research: To analyze the relationship of public perception through the Theory of Planned Behavior approach with the intention to treat toothache. Research Methods: The type of research used is analytic observational with cross sectional. Sampling was done by using a porpusive sampling technique. The research sample amounted to 113 respondents. Data were obtained by questionnaires distributed to the public and analyzed by the Spearman'rho statistical test. The results: showed that 51% of respondents had moderate intentions, 52.2% of respondents had moderate attitudes, 50.4% of respondents had high subjective norms and 51.3% of respondents had moderate behavioral control. Attitude variables had a significant relationship with treatment intentions. toothache (p value = 0.000), subjective norm has a relationship with the intention to treat toothache (p value = 0.000) and behavioral control has a relationship with the intention to treat toothache (p value = 0.000). Conclusions: Public perception through the Theory of Planned Behavior approach has a relationship with the intention to treat toothache.